Development of Wondershare Filmora Food Photography Learning Media in Culinary Arts Course at Medan State University - Icha, Yarisya Ferika; Esi Emilia; Fatma Tresno Ingtyas; Ana Rahmi; Cucu Cahyana; Rachmat Mulyana (Jurnal Sains Boga, 2023)
This research aims to: (1) Produce Wondershare Filmora-based learning media in Culinary Arts Subject; (2) Test the feasibility of Wondershare Filmora-based learning media in Culinary Arts Subject according to material experts and media experts. The research location was conducted at the Culinary Education Study Program at Medan State University. The research time was November 2022 - January 2023. This research uses the ADDIE development model which is limited to 3 steps, namely (1) Analysis (needs analysis); (2) Design (making storyboards and making learning media); (3) Development (validation by material experts and media experts). The research subjects consisted of one material expert, one media expert, and 30 students of the Cosmetology Education Study Program. The data collection technique used a questionnaire to capture material quality data and media quality data. The data analysis technique was descriptive. Based on the results of this study, the results of the analysis of the needs of lecturers and students that all lecturers and students need Wondershare Filmora learning media, each score ≥ 50 percent. This media can be disseminated and implemented in the Culinary Arts course. The results of the material expert validation obtained a feasibility of 95.38 percent with the criteria "Very Feasible", and the results of the media expert validation obtained a feasibility of 94.12 percent with the criteria "Very Feasible" so that Wondershare Filmora media learning in the Culinary Arts course Food Photography material is included in the "Very Feasible" category with an average value of 94.75 percent. The results of student assessment of student response trials of Wondershare FIlmora learning in Culinary Arts courses Food Photography material are very high with a score of 4.63.